Early Modern England and Islamic Worlds
XV, 272 p.
Keywords: The essays in this book analyze a range of genres and considers geographical areas beyond the Ottoman Empire to deepen our post-Saidian understanding of the complexity of real and imagined "traffic" between England and the "Islamic worlds" it encountered and constructed.